Linking coach interpersonal style with Athlete doping intentions and doping use: A prospective study - Ntoumanis, Nikos; Barkoukis, V.; Gucciardi, Daniel; Chan, Derwin (Human Kinetics, 2017)
Â© 2017 Human Kinetics, Inc. We brought together various lines of work on motivation, morality, and doping by testing a theory-based model prospectively linking contextual and personal motivational variables, moral attitudes, moral disengagement in doping, doping intentions, and doping use. Participants were 257 Greek athletes who completed a questionnaire pack at the beginning of a sport season. In the case of doping use, we also obtained data close to the end of the same season. The model showed that perceptions of controlling coach behaviors predicted athlete need frustration, which in turn predicted low moral functioning and doping intentions/doping use. The findings highlight pathways (direct and indirect) bywhich the social environmentmay impact on athletes' intentions and decisions to engage in doping and could pave the way for future antidoping interventions aimed at improving coaching interpersonal style.